Hospital Acquired Infections in COVID-19 patients in sub intensive care unit - Castaldi, Silvana; Luconi, Ester; Marano, Giuseppe; Auxilia, Francesco; Maraschini, Anna; Bono, Patrizia; Ungaro, Riccardo; Bandera, Alessandra; Boracchi, Patrizia; Biganzoli, Elia (Acta Biomedica Atenei Parmensis, 2020)
The aim of this study is to assess the association among species of bacteria and to identify the presence of clusters of patients in sub intensive care unit with different profiles of infection, and to study the relationship between such profiles and patient demographics (gender, age), kind of investigations and  material used to detect the infection. The findings need to analyse a bigger amount of data in the same setting to make evident that it is constant the infection only with Escherichia coli and Staphylocossus epidemidis and a third case in which more bacteria are inlvolved.